2015
DOI: 10.1007/s11926-015-0532-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Jo-1 in the Immunopathogenesis of the Anti-synthetase Syndrome

Abstract: Histidyl-tRNA synthetase (HRS = Jo-1) represents a key autoantibody target in the anti-synthetase syndrome that is marked by myositis as well as extra-muscular organ complications including interstitial lung disease (ILD). Over the last 25 years, a wealth of clinical, epidemiological, genetic, and experimental data have collectively supported a role for Jo-1 in mediating deleterious cell-mediated, adaptive immune responses contributing to the disease phenotype of the anti-synthetase syndrome. Complementing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
1
23
0
5
Order By: Relevance
“…This disease is a heterogeneous group of autoimmune disease characterized by interstitial lung disease (ILD), myositis, mechanic's hands, Raynaud's phenomenon, and arthritis 61 . Up to now, there are mainly eight anti-ARS autoantibodies including anti-histidyl (anti-Jo-1), anti-alanyl (anti-PL-12), anti-threonyl (anti-PL-7), anti-asparaginyl (anti-KS), anti-glycyl (anti-EJ), anti-phenylalanyl (anti-Zo), anti-tyrosyl (anti-Ha), and anti-isoleucyl (anti-OJ) in ASSD 62,63 . Among them, anti-Jo-1 antibody is the most common.…”
Section: Arss and Autoimmune Diseasesmentioning
confidence: 99%
“…This disease is a heterogeneous group of autoimmune disease characterized by interstitial lung disease (ILD), myositis, mechanic's hands, Raynaud's phenomenon, and arthritis 61 . Up to now, there are mainly eight anti-ARS autoantibodies including anti-histidyl (anti-Jo-1), anti-alanyl (anti-PL-12), anti-threonyl (anti-PL-7), anti-asparaginyl (anti-KS), anti-glycyl (anti-EJ), anti-phenylalanyl (anti-Zo), anti-tyrosyl (anti-Ha), and anti-isoleucyl (anti-OJ) in ASSD 62,63 . Among them, anti-Jo-1 antibody is the most common.…”
Section: Arss and Autoimmune Diseasesmentioning
confidence: 99%
“…In our case, the sequence of the first 60 amino acids of HisRS (UniProtKB identifier P12081) was examined to predict peptides that can bind DRB1*03:01; residues 11-23 (HisRS 11-23 ) contained 2 such motifs and therefore had a high probability of containing a bona fide DRB1*03:01 epitope. Thus, HisRS [11][12][13][14][15][16][17][18][19][20][21][22][23] peptide was selected for further functional assays ( Figure 1A). Immunohistochemistry and histopathology.…”
Section: Identification Of the Hisrs T Cell Epitopementioning
confidence: 99%
“…In 1999, Wakasugi and Schimmel identified that these synthetases may act as cytokines, assisting in cell death and recruitment of inflammatory cells (22). Further studies, summarized by Ascherman in 2015, have identified innate and adaptive immunity in the pathogenesis of anti-synthetase syndrome (23). …”
Section: Diagnosismentioning
confidence: 99%